Genetic markers of the stress generation model: A systematic review. (October 2021) - Bahji, Anees; Forth, Evan; Hargreaves, Tegan; Harkness, Kate
Highlights: Robust evidence suggests that depression, and risk for depression, are associated with the generation of stressful life events. This systematic review aimed to identify specific molecular genetic markers associated with the generation of stressful life events. There is evidence that genetic variation in the serotonin, HPA axis, and oxytocin systems moderates the effects of psychosocial vulnerability markers on the generation of proximal, dependent life events. Future research should examine additional genetic markers in systems known to confer risk for stress generation. Abstract: Aim: Robust evidence suggests that depression, and risk for depression, are associated with the generation of stressful life events. This tendency to generate stress may be genetically determined. This systematic review aimed to identify specific molecular genetic markers associated with the generation of interpersonal stressful life events, at least in part dependent on individuals' behavior. Method: We followed the PRISMA guidelines in searching six electronic databases (PubMed, MEDLINE, PsycINFO, CINAHL, Cochrane, and EMBASE) from inception to January 2021, and we reviewed the reference lists of eligible articles for additional records. We restricted eligibility to empirical studies involving at least one genetic marker and including proximal life events. We evaluated the risk of bias using the Newcastle Ottawa Scale for observational studies. The outcome permitted a distinction between life events dependent on the individual's agency versus independent events. Results: Seven studies, including 3585 participants, met eligibility criteria. Three were longitudinal, and four were cross-sectional; six included adolescents and young adults, and one focused on middle adulthood. Four examined the serotonin-transporter-linked promoter region (5-HTTLPR), two examined the rs53576 single nucleotide polymorphism of the oxytocin receptor gene (OXTR), and one examined a multilocus genetic profile score including four hypothalamic-pituitary-adrenal (HPA) axis genes. There were no significant direct correlations between genotype and life events in any study. Instead, their relation was significantly moderated by symptoms, exposure to early adversity, or attachment. Consistent with the stress generation hypothesis, this moderation relation was significant in predicting exposure to dependent life events but was not significant in predicting independent life event exposure. Conclusions: There is evidence that genetic variation in the serotonin, HPA axis, and oxytocin systems moderates the effects of psychosocial vulnerability markers on the generation of proximal, dependent life events. Future research should examine additional genetic markers in systems known to confer risk for stress generation. PROSPERO: CRD42019136886.